Measurable residual disease-guided treatment with azacitidine to prevent haematological relapse in patients with myelodysplastic syndrome and acute myeloid leukaemia (RELAZA2): an open-label, multicentre, phase 2 trial - Platzbecker, Uwe; Krämer, Alwin; Bochtler, Tilmann (The lancet. Oncology, 2018)
Background - Monitoring of measurable residual disease (MRD) in patients with advanced myelodysplastic syndromes (MDS) or acute myeloid leukaemia (AML) who achieve a morphological complete remission can predict haematological relapse. In this prospective study, we aimed to determine whether MRD-guided pre-emptive treatment with azacitidine could prevent relapse in these patients. - Methods - The relapse prevention with azacitidine (RELAZA2) study is an open-label, multicentre, phase 2 trial done at nine university health centres in Germany. Patients aged 18 years or older with advanced MDS or AML, who had achieved a complete remission after conventional chemotherapy or allogeneic haemopoietic stem-cell transplantation, were prospectively screened for MRD during 24 months from baseline by either quantitative PCR for mutant NPM1, leukaemia-specific fusion genes (DEK-NUP214, RUNX1-RUNX1T1, CBFb-MYH11), or analysis of donor-chimaerism in flow cytometry-sorted CD34-positive cells in patients who received allogeneic haemopoietic stem-cell transplantation.
Gesehen am 23.04.2020